Effects of intracerebroventricular injections of losartan or PD123319 on arterial pressure and heart rate of sodium replete and sodium deplete rats - De Luca Jr., Laurival A. [UNESP]; Barbosa, Silas P. [UNESP]; Sugawara, Alexandre M. [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier, 1996)
Angiotensin II (Ang II) non-peptide antagonists were injected i.c.v. (6.25-200 nmol, n = 5-8 rats/group): In sodium replete rats, losartan (AT1 receptor antagonist) induced an increase in mean arterial pressure (MAP) and in heart rate (HR) by 3rd ventricular (3rdV) injection, and a weaker pressor response and bradycardia by 4th ventricular (4thV) injection. PD123319 (AT2 receptor antagonist) induced an increase in MAP and in HR by 3rdV injection, and an increase in MAP and no alteration in HR by 4thV injection. In sodium deplete (furosemide plus removal of ambient sodium for 24 h) rats, losartan induced an increase in MAP and no alteration in HR by 3rdV injection, and no alteration in MAP and bradycardia by 4thV injection. PD123319 induced an increase in MAP and in HR by 3rdV injection, and an increase in MAP and bradycardia by 4thV injection. Thus, there was no fall in MAP by central injections of Ang II antagonists. Intravenous injection of losartan, but not of PD123319, induced a fall in MAP in both sodium replete and sodium deplete animals. Therefore, losartan and PD123319 can have similar effects on MAP and HR when injected intracerebroventricularly, although some differences are also present. The bradycardia is consistent with an withdrawal of Ang II inhibitory action on baroreflex.
Keywords: Angiotensin II; Angiotensin receptor subtype; AT1 receptor; AT2 receptor; Sodium depletion; 1 (4 dimethylamino 3 methylbenzyl) 5 diphenylacetyl 4,5,6,7 tetrahydro 1h imidazo[4,5 c]pyridine 6 carboxylic acid; angiotensin 1 receptor; angiotensin 2 receptor; angiotensin 2 receptor antagonist; furosemide; losartan; animal experiment; arterial pressure; controlled study; heart rate; intracerebroventricular drug administration; male; nonhuman; pressoreceptor; priority journal; rat; sodium depletion; Animals; Biphenyl Compounds; Blood Pressure; Cohort Studies; Heart Rate; Imidazoles; Injections, Intraventricular; Losartan; Male; Pyridines; Rats; Receptors, Angiotensin; Sodium; Tetrazoles; Animalia; Theilovirus